Analisa Peluang dan Ancaman/Tantangan Perdagangan Produk Perkebunan (Studi Kasus Pada Perdagangan Indonesia dan Jepang) - Novia Citra; Daspar (CV. ITTC INDONESIA, 2025)
This study examines the opportunities and challenges in the trader of plantation products between Indonesia dan Japan within the context of international trade. The analysis focuses on identifying comparative advantages and trade barriers in the export of commodities such as palm oil, rubber, and coffee. Secondary data from 2021 to 2023 indicate that Indonesia holds significant potential in the production and export of plantation products, while Japan represents a promising market with strong demand for eco-friendly and high-quality goods. However, challenges such as strict quality standards, tariff and non-tariff barriers, and global price volatility pose significant threats. By adopting strategies such as products diversification, quality enhancement, and proactive diplomacy, Indonesia has the potential in the Japanese market